The treatment of bacterial biofilms cultivated on knee arthroplasty implants using the bioelectric effect - Tamimi, Iskandar; Gasca, María; Halbardier, Alexandra; Martin, Sergio; Martin Caballero, Gregorio; Lucena Serrano, Cristina; Martin, Elena; Tamimi, Faleh; González-Quevedo, David; García de Quevedo, David; Sobrino, Beatriz; Palop, Begoña; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
The aim of this study was to analyze the effectiveness of the bioelectric effect in the elimination of bacterial biofilm on cultivated knee arthroplasty implants. 4-femoral prosthetic implants were cultivated with a staphylococcus aureus inoculum for 15 days. The components were divided into 4 different groups: A (not treated), B (normal saline 20-minutes), C (bioelectric effect 10-minutes), D (bioelectric effect 20-minutes). The implants were sonicated, and the detached colonies were quantified as the number of colony-forming-units (CFUs). The implants were sterilised and the process was repeated in a standardized manner 4 more times, to obtain total of 5 samples per group. The number of the CFUs after a 10-minute exposure to the bioelectric effect was of 208.2± 240.4, compared with 6,041.6 ± 2010.7 CFUs in group A, representing a decrease of 96.5% ± 4.3 (p=0.004). And a diminution of 91.8% ± 7.9 compared with 2,051.0 ± 1,364.0 CFUs in group B (p = 0.109). The number of bacterial colonies after a 20-minute exposure to the bioelectric effect was 70 ± 126.7 CFUs, representing a decrease of 98.9% ± 1.9 (p=0.000) compared with group A. And a decrease of 97.8% ± 3.0 (p=0.019) compared with group B.The bioelectric effect was effective in the elimination of bacterial biofilm from knee arthroplasty implants. This method could be used in the future as part of conventional surgical procedures.